PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON EQUITY (ROE) TERHADAP Z-SCORE ALTMAN PADA PT RAMAYANA LESTARI SENTOSA Tbk. 2014-2023 - Qoriyati Qoriyati; Amthy Suraya (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effect of Debt to Equity Ratio (DER) and Return on Equity (ROE) on Altman's Z-Score as an indicator of financial health at PT Ramayana Lestari Sentosa Tbk during the period 2014–2023. Altman's Z-Score is a bankruptcy prediction method that combines several financial ratios and is widely used in assessing a company's financial risk. DER describes the proportion of debt to equity, while ROE measures the company's efficiency in generating profits from its own capital. The research method used is quantitative descriptive with a multiple linear regression approach. Data were obtained from the company's annual financial statements for 10 years, then analyzed using the SPSS version 22 statistical tool. The results showed that DER partially had a negative and significant effect on Altman's Z-Score, while ROE partially had a positive and significant effect on Altman's Z-Score. Simultaneously, DER and ROE had a significant effect on Altman's Z-Score.